2010
DOI: 10.1111/j.1365-2567.2010.03351.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat eosinophils stimulate the expansion of Cryptococcus neoformans-specific CD4+ and CD8+ T cells with a T-helper 1 profile

Abstract: Summary Experimental Cryptococcus neoformans infection in rats has been shown to have similarities with human cryptococcosis, revealing a strong granulomatous response and a low susceptibility to dissemination. Moreover, it has been shown that eosinophils are components of the inflammatory response to C. neoformans infections. In this in vitro study, we demonstrated that rat peritoneal eosinophils phagocytose opsonized live yeasts of C. neoformans, and that the phenomenon involves the engagement of FcγRII and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 51 publications
0
31
1
7
Order By: Relevance
“…Eosinophils have been mentioned before in murine models of cryptococcosis, 10,23,[41][42][43] observed in human cryptococcosis, 44 -46 and described with an emphasis on tissue damage. 41 Although in vitro eosinophils have phagocytosed C. neoformans 23 and presented cryptococcal antigens, 47 in vivo, no evidence for uptake of C. neoformans by eosinophils has been found by others 4 and in this study (data not shown). Herein, we highlight an immunoregulatory role of eosinophils that contribute to IL-4 -dependent immunopathological features during murine pulmonary C. neoformans infection.…”
Section: Discussioncontrasting
confidence: 59%
“…Eosinophils have been mentioned before in murine models of cryptococcosis, 10,23,[41][42][43] observed in human cryptococcosis, 44 -46 and described with an emphasis on tissue damage. 41 Although in vitro eosinophils have phagocytosed C. neoformans 23 and presented cryptococcal antigens, 47 in vivo, no evidence for uptake of C. neoformans by eosinophils has been found by others 4 and in this study (data not shown). Herein, we highlight an immunoregulatory role of eosinophils that contribute to IL-4 -dependent immunopathological features during murine pulmonary C. neoformans infection.…”
Section: Discussioncontrasting
confidence: 59%
“…Fc receptor repertoires and functions are not directly transposable between mice and humans (47); unlike mouse eosinophils, human peripheral blood eosinophils constitutively express FcγRIIA (21, 48), which, like mouse FcγRIII, is an activating receptor (47). A number of in vitro studies using eosinophils from rodents and human blood demonstrate that exposure of eosinophils to immune complexes or cross-linking eosinophil-expressed Fc gamma receptors elicits eosinophil activation (22), degranulation of cationic granule proteins (21, 25, 49), growth factor (23) and cytokine secretion (50, 51), superoxide production (25), enhanced survival (24), and antigen presenting cell functions to expand both CD4 + and CD8 + lymphocytes (51). Our data shown here now provide a mechanism by which these known Fc gamma receptor-dependent functions may be linked to resident intestinal eosinophils in vivo in secondary immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are less studied, other types of innate immune cells are found in granulomas and may play a role in defense against cryptococcosis (29). The presence of either excess eosinophils or excess neutrophils is associated with poor control of infection in mice (30, 31), whereas eosinophils might have a beneficial role in rats (32). …”
Section: Introduction To the Biology Of Cryptococcus Neoformansmentioning
confidence: 99%